CONVERSION OF RICE LAND INTO RESIDENTIAL AREA IN PAYAKUMBUH CITY, 2012-2022 - Muhammad Irsyad; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine 1) Changes in paddy field land cover to other land uses in Payakumbuh City from 2012 – 2022, 2) The process of changing paddy fields into residential areas in 2012 – 2022. The research method used in this study was a mixed research method (mixed method). Based on the research results, the research results obtained 1) Changes from paddy fields to other land uses from 2012 to 2022 covering an area of ​​67.96 ha. Paddy fields turned into bodies of water, open land, shrubs, plantations and settlements. 2) The process of conversion of paddy fields in Payakumbuh City is gradual with sporadic patterns and multi-form or no-form conversion. Keywords : Land conversion, Ricefield, Settlement.